2005
DOI: 10.1139/f05-033
|View full text |Cite
|
Sign up to set email alerts
|

A model of aquaculture biodeposition for multiple estuaries and field validation at blue mussel (Mytilus edulis) culture sites in eastern Canada

Abstract: Development of mariculture in Canadian waters has outpaced the ability of regulators to adequately assess environmental impacts and coexistence with other resource users. In eastern Canada, suspended longline culture of blue mussels (Mytilus edulis) leads to depletion of seston and subsequent biodeposition of feces and pseudofeces. Based on the need to evaluate aquaculture effects over multiple farms, a model was developed to compare the rate of mussel egestion with the scale of culture and tidal flushing of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…The overall influence of mussel aquaculture on benthic communities is likely to be affected by a number of factors such as local primary production, hydrodynamic features of the site, size, biomass and age of the shellfish farm (Grant et al 2005, Miron et al 2005. Results from our study showed significant differences in the composition and structure of the epibenthic macrofaunal component of benthic communities at the different mussel farms.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The overall influence of mussel aquaculture on benthic communities is likely to be affected by a number of factors such as local primary production, hydrodynamic features of the site, size, biomass and age of the shellfish farm (Grant et al 2005, Miron et al 2005. Results from our study showed significant differences in the composition and structure of the epibenthic macrofaunal component of benthic communities at the different mussel farms.…”
Section: Discussionmentioning
confidence: 69%
“…The scales over which bivalve aquaculture influence the environment may then depend on the precise variable studied (e.g. physicochemical features, biodeposition, infaunal or epibenthic assemblages) (Hartstein & Rowden 2004, Grant et al 2005, Miron et al 2005, Richard et al 2007). For example, the effects of sediment enrichment on infaunal assemblages may be limited to tens of meters whereas the effects on more mobile invertebrates may extend to hundreds of meters.…”
Section: Introductionmentioning
confidence: 99%
“…In the Gulf of St. Lawrence region, mussel farms are usually established in relatively shallow coastal areas (e.g. 3 to 5 m; Grant et al 2005) as compared to other areas (e.g. 8 to 42 m in New Zealand; Hartstein & Stevens 2005) and characterised by low current velocities.…”
Section: Estimated Dispersion Of Mussel Biodepositsmentioning
confidence: 99%
“…mussels, oysters) located at sites with slower currents and less resuspension suffered measurable degradation (e.g. sulfide production, nutrient release) with high POM accumulation (Grant et al 2005, Holyoke 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Many types of models have been used to compute biodeposition associated with shellfish aquaculture (Grant et al 2005, Weise et al 2009), stock production (Gangnery et al 2001, Duarte et al 2003, carrying capacity (Byron et al 2011), and ecosystem effects and linkages (Ren et al 2012). From a biogeochemical perspective, numerical models can be used to quantify the spatial and temporal impacts of aquaculture-derived POM deposition on underlying sediments and how these impacts are related to farm size, culture intensity, and the physical environment of the aquaculture site.…”
Section: Introductionmentioning
confidence: 99%